Developmental progression of lymphatic valve morphology and function - Davis, Michael J.; Zawieja, Scott D.; Yang, Ying (Frontiers in Cell and Developmental Biology, 2024)
Introducon. The bicuspid valves found in collecng lymphac vessels and some veins are essenal for maintaining the unidireconal flow that is important for both lymphac and venous funcon. Under an adverse pressure gradient, the two valve leaflets ghtly overlap to prevent backflow. Valves are proposed to share 4 main stages of development, based on images obtained from randomly orientated valves in fixed mouse embryos (Bazigou et al., 2009;Sabine et al., 2012), with the best structural views obtained from larger, venous valves (Bazigou et al., 2011). It is not known at what stage lymphac valves (LVs) become funconal (e.g., able to oppose backflow), although a requirement for stage 4 is presumed.To gain insight into this sequence of events for LVs, we took advantage of Prox1CreER T2 ;Foxo1 f/f mice and Foxc2CreER T2 ;Foxo1 f/f mouse models, in which deleon of the valve repressor factor Foxo1 promotes the development of new LVs in adult lymphac vessels. Both strains also contained a Prox1eGFP reporter for imaging. Mesenteric collecng lymphac vessels were dissected, cannulated, and pressurized for ex vivo tests of valve funcon. LVs at various stages (1-4 and intermediate) were idenfied in mul-valve segments, which were subsequently shortened to perform tests of back leak on single valves. The GFP signal was then imaged at high magnificaon on a confocal microscope. Z-stack reconstrucons allowed 1:1 comparisons of LV morphology with quantave measurement of back leak.Results. As expected, LVs from stages 1-3 were completely leaky. Stage 4 valves were generally not leaky. A high percentage of valves at an intermediate stage (3.5), in which there was inseron of a second commissure but without proper luminal alignment, effecvely resisted back leak in the face of elevated oulow pressure. Discussion. Our findings represent the first 3D images of developing lymphac valves and indicate that valves become competent between stages 3 and 4 of development.